The Effect of Compensation and Work Environment Mediated by Job Satisfaction on Employee Performance in Automotive Companies in Batam - Ricky Lim; Yuli Indah Fajar Dini (Jurnal Bisnis dan Manajemen, 2023)
The performance of employees can be influenced by various factors, including compensation and the work environment. When employee compensation and the working environment are favorable, it can lead to an improvement in employee performance. This study seeks to examine the impact of compensation and the work environment on employee performance within automotive companies in Batam City, with job satisfaction as a mediating factor. The research methodology employs Structural Equation Modeling (SEM) analysis using SmartPLS. The study encompasses 401 employee respondents from automotive companies in Batam City. The findings reveal that both compensation and the work environment significantly and positively affect job satisfaction. Furthermore, job satisfaction significantly influences employee performance, and the combined impact of compensation and the work environment on employee performance is significantly positive, mediated by job satisfaction.